PENGARUH TIPE KEPRIBADIAN CONVENTIONAL, ADVERSITY QUOTIENT, DAN MOTIVASI BERPRESTASI PADA KINERJA AKADEMIK MAHASISWA MAGISTER AKUNTANSI - Ristadewi, Ida Ayu Arie; Ratnadi, Ni Made Dwi; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study aimed to get empirical evidence of the effect of conventional personality type, adversity quotient, and achievement motivation in master of accounting student’s academic performance. Conventional personality type according to Holland theories of vocational personalities and work environment is measured using Self-Directed Search questionnaire. Adversity Quotient is measured using Adversity Response Profile questionnaire and achievement motivation is measured using Work and Family Orientation questionnaire. Determination of the sample use saturated sampling techniques. The research data consisted of primary data obtained through questionnaires and secondary data related to GPA student. Data were analyzed using multiple linear regression analysis. The analysis shows that the higher the conventional personality type then the higher student’s academic performance was. Adversity Quotient and achievement motivation do not increase master of accounting student’s academic performance.
Keywords: Academic Performance, Personality Theory, Conventional Personality Type, Adversity Quotient, Achievement Motivation